Charitable activity of women in Nizhny Novgorod region in the 1870s – 1890s - Ekaterina Zapevalova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article considers women's charitable activities in the Nizhny Novgorod region in the 1870-1890s. In the XIX century women were especially social active in the field of charity. The involvement of women in the social life of the province affected mainly upper and wealthy groups of the urban population (in the peasant group the features of traditional society were preserved for a long time). The article presents new facts (found both in archival and published sources) about the philanthropy of Nizhny Novgorod merchantry and nobility. The facts demonstrate that charitable initiatives of charity activists manifested themselves mainly in their social and cultural projects. In article all donations of women are systematized by type of assistance (assistance to the poor and the church, maintenance of almshouses, donations for the construction of hospitals and maternity hospitals, charity in the field of education, donations to orphanages, registration of wills for the needs of philanthropy). It is concluded that the largest amount of donations in monetary terms in the last third of the XIX century was ordered for the construction of new hospitals. For the first time, the article presents a detailed history of the hospital institution, created with a large donation from the merchant G.N. Ryabinina for a building of surgical department of the Nizhny Novgorod Provincial Zemstvo Hospital in 1899.